Pathogen-specific changes in composition and quality traits of milk from goats affected by subclinical intramammary infections. Issue 2 (26th May 2021) - Bezerra, Andreia B.; de Leon, Candice M. C. G.; Givisiez, Patrícia E. N.; Silva, Núbia M. V.; Santos Filho, Lauro; Pereira, Walter Esfraim; Pimenta Filho, Edgard C.; Azevedo, Paulo S.; Oliveira, Celso J. B.
Abstract: We investigated the effects of pathogens associated with subclinical intramammary infections on yield, composition and quality indicators of goat milk. By means of a longitudinal study, individual half udder milk samples ( n = 132) were collected at different lactation periods and assessed for milk yield and physicochemical composition, somatic cell count (SCC), total bacteria count (TBC) and microbiological culture. Staphylococci species accounted for the great majority of the isolates (96.1%). Intramammary infections significantly reduced fat and total solids in goat milk and increased both SCC and TBC. However, these indicators were significantly higher in udder halves affected by S. aureus compared with other staphylococci species.